Push-pull to manage leaf-cutting ants: an effective strategy in forestry plantations - Perri, Daiana Vanesa (2020)
BACKGROUND: Leaf-cutting ants (LCAs) are amongst the most important forestry pests in South America. Currently, their control is carried out almost exclusively through the application of toxic baits of restricted use. Here we evaluate a push-pull strategy (i.e., the simultaneous use of attractant and repellent stimuli in order to divert pests) to manage LCAs Acromyrmex spp. in young willow plantations in the area of Delta of the Parana River, Argentina, a wetland ecosystem. First, we surveyed ants' selection of farmland vegetation during one year. Then, we estimated ants' preferences between the willow Salix babylonica and a subsample of plant species from farmland vegetation under laboratory conditions. Finally, we designed and performed a fully crossed experimental field assay to evaluate a push-pull strategy by using farmland vegetation as pull stimulus. RESULTS: We surveyed 39 plant species in the area, 19 of which had been foraged by LCAs along the year. Plants were selected by species, not by abundance. In the lab, ants showed similar preference for the cultivated willow and the subsample of plant species. Push-pull was the only treatment that maintained willow remaining vegetation above 60–80% at the end of the growing season. CONCLUSIONS: For the first time the push-pull strategy was evaluated in social insects. We demonstrated that it can be successfully used to manage LCAs in young willow plantations. Our strategy generates biodiversity, which can improve the ecosystem functioning, and it can be easily implemented by producers since its design is based on regular willow plantations.